What Is the Role of Patient Families? An Exploratory Study in a Medical Intensive Care Unit. (September 2017) - Papautsky, Elizabeth Lerner; Abdulbaseer, Ummesalmah; Faiola, Anthony
Patient safety and quality efforts recently began to emphasize patient and family engagement in medical decision making. With measures primarily focused on satisfaction, challenges exist around understanding the impact of engagement on patient outcomes. Research is needed to understand the role of patient/family in safety and quality across clinical environments. The current exploratory study uses observations, ad hoc interviews, and questionnaires to capture the perspective of clinicians and staff on a Medical Intensive Care Unit regarding presence and engagement of families in patient care. Findings suggest that reported roles go beyond emotional support and further investigation is needed to explore the role of families in patient care from the safety and quality perspective.